Insulin-Like Growth Factor 2 and the Insulin Receptor, But Not Insulin, Regulate Fetal Hepatic Glycogen Synthesis - Liang, Li (The Endocrine Society, 2010)
Whether insulin or IGFs regulate glycogen synthesis in the fetal liver remains to be determined. In this study, we used several knockout mouse strains, including those lacking Pdx-1 (pancreatic duodenal homeobox-1), Insr (insulin receptor), and Igf2 (IGF-II) to determine the role of these genes in the regulation of fetal hepatic glycogen synthesis. Our data show that insulin deficiency does not alter hepatic glycogen stores, whereas Insr and Igf2 deficiency do. We found that both insulin receptor isoforms (IR-A and IR-B) are present in the fetal liver, and their expression is gestationally regulated. IR-B is highly expressed in the fetal liver; nonetheless, the percentage of hepatic IR-A isoform, which binds Igf2, was significantly higher in the fetus than the adult. In vitro experiments demonstrate that Igf2 increases phosphorylation of hepatic Insr, insulin receptor substrate-2, and Akt proteins and also the activity of glycogen synthase. Igf2 ultimately increased glycogen synthesis in fetal hepatocytes. This increase could be blocked by the phosphoinositide 3-kinase inhibitor LY294008. Taken together, we propose Igf2 as a major regulator of fetal hepatic glycogen metabolism, the insulin receptor as its target receptor, and phosphoinositide 3-kinase as the signaling pathway leading to glycogen formation in the fetal liver.